MASYARAKAT MINDANAO, ABU SAYYAF DAN MASALAH KEAMANAN KAWASAN - Al Chaidar; M Akmal; Saifullah Ali; Nanda Amalia; Dara Quthni Effida; Herdi Sahrasad (Universitas Kristen Satya Wacana, 2018)
ABSTRACT This article explores on the Abu Sayyaf radical movement, prospects for security in Sulawesi and Sulu sea is done by field research, to Mindanao and border islands in Sulu, Southern Philippines, our neighboring country. This study not only uses a security approach, but also a welfare and socio-cultural approach, believing that finding the root cause of Bangsamoro Philippines is the most important thing to do and look for a way out. Unfortunately, the Muslim Moro relationship with the Manila Government in many cases means confrontation and demands for free will. The Filipino Muslims, the Moros, believe that they must fight for their security of life and security, live according to the values ​​they believe in, have the power to decide their fate, this is what they continue to strive for. We are a predominantly Muslim nation of Indonesia, hoping that the struggle finds its culmination and the creation of peace in this highly dynamic region of culture, commerce, politics and science could be achieved.